Penerapan Strategi Pembelajaran Untuk Meningkatkan Aspek Moral Agama Pada Anak Usia Dini - Yasmin, Mita Amalia; Azhari, Marini Wulan; Hardiyana, Andri (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early childhood is a very important period in the development of children's character and personality, which is often referred to as the golden age. At this age, children tend to imitate the behavior of adults around them, so the role of parents and educators is very crucial in providing good examples. Early childhood education (PAUD) covers the age range of 0-8 years and involves various educational institutions such as Kindergartens (TK) and Child Care Centers (TPA). One important aspect in PAUD is moral development, which is the basis for forming children's character. The development of religious morals in early childhood includes the introduction of God, good and bad behavior, and religious values ​​that are adhered to. This study aims to identify learning strategies that can improve moral aspects in early childhood, with a focus on habituation through daily activities such as prayer, reading short letters, and storytelling. The data collection technique used was through the process of observation and interviews, and the approach used in this study was a qualitative approach. The results of the study showed that the habituation method, including the use of audiovisual media, can be effective in instilling religious moral values ​​in children. In addition, collaboration between teachers and parents is very important in strengthening religious moral education at home and school.